2016
DOI: 10.1007/s12038-016-9602-4
|View full text |Cite
|
Sign up to set email alerts
|

Differential expression of carotenoid biosynthetic pathway genes in two contrasting tomato genotypes for lycopene content

Abstract: Tomato (Solanum lycopersicum L.) is one of the model plant to study carotenoid biosynthesis. In the present study, the fruit carotenoid content were quantified at different developmental stages for two contrasting genotypes, viz. IIHR-249-1 and IIHR-2866 by UPLC. Lycopene content was high in IIHR-249-1 (19.45 mg/100 g fresh weight) compared to IIHR-2866 (1.88 mg/100 g fresh weight) at the ripe stage. qPCR was performed for genes that are involved in the carotenoid biosynthetic pathway to study the difference i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…The red-colored tomato fruit mainly contains lycopene (red carotenoid), which accounts for 90% of the total carotenoid content, and β-carotene (yellow carotenoid). Lycopene is catalyzed by lycopene β-cyclase (CYC-B) to form β-carotene, and the ratio of these two carotenoids affects the fruit color [ 23 ]. As expected, the carotenoid content of the psy1 single mutant was significantly lower than that of other genotypes because of the abnormal accumulation of lycopene ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The red-colored tomato fruit mainly contains lycopene (red carotenoid), which accounts for 90% of the total carotenoid content, and β-carotene (yellow carotenoid). Lycopene is catalyzed by lycopene β-cyclase (CYC-B) to form β-carotene, and the ratio of these two carotenoids affects the fruit color [ 23 ]. As expected, the carotenoid content of the psy1 single mutant was significantly lower than that of other genotypes because of the abnormal accumulation of lycopene ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Our previous work reported that the transcript level of CYC-B regulates orange color in tomato fruit [16]. Researchers focused on carotenoid content [17, 35] were also reported that regulation of CYC-B increases the accumulation of β-carotene in the tomato fruit during ripening. Similar results were observed during fruit development in bell pepper, a related species [3639].…”
Section: Resultsmentioning
confidence: 99%
“…This study will help to improve our understanding of the processes involved in regulating flower development, nectar biosynthesis, and nectary development in pepper flowers. More contigs and unigenes were reported compared to previous transcriptomic studies in other plants, such as tomato (Pandurangaiah et al, 2016), potato (Cao et al, 2016), and eggplant (Ramesh et al, 2016), which indicated that pepper contains abundant gene resources. We believe that our data will help to provide important new insights and facilitate further studies on pepper genes and their functions.…”
Section: Global Gene Expression Patterns In Pepper Flowersmentioning
confidence: 85%